Application of internal fixator system for anterior pelvic ring with simultaneous application of sacroiliac screw internal fixation of the posterior pelvic ring in Tile C-type unstable pelvic fractures - Liu, Zhongbing; Zou, Guoyou (Vojnosanitetski pregled, 2024)
Background/Aim. The number of pelvic traumas is increasing globally, mostly due to car accidents but also due to an increasing number of sports and recreational traumas. Tile C-type unstable pelvic trauma (TCUPT) is a kind of high-energy trauma that occurs during traffic accidents or accidents when falling from big heights. The aim of our study was to explore the application of the internal fixation (INFIX) system for the anterior pelvic ring (APR) with simultaneous application of sacroiliac screw (SS) INFIX of the posterior pelvic ring (PPR) in TCUPT. Methods. The subjects (89 of them in total) were recruited among patients with TCUPT from December 2020 to December 2023. A retrospective analysis of the subjects’ data was performed, after which the subjects were divided into two groups based on different therapeutic regimens applied: group A (INFIX system for the APR + SS INFIX of the PPR, n = 46) and group B (external fixator for the APR + SS INFIX of the PPR, n = 43). Results. In comparison with group B, group A had a shorter period before the commencement of the first activity after surgery, shorter fracture healing time and joint function recovery time, as well as length of hospital stay (t = 6.623, 4.796, 7.992, and 5.227, respectively, p  0.05). The fracture reduction outcomes were better in group A than in group B (Z = 2.058, p
Keywords: bone screws; fractures, bone; fracture fixation, internal; open fracture reduction; pelvic bones; orthopedic procedures; treatment outcome